Feasibility of Using a Novel 2.45 GHz Double Short Distance Slot Coaxial Antenna for Minimally Invasive Cancer Breast Microwave Ablation Therapy: Computational Model, Phantom, and In Vivo Swine Experimentation. (8th May 2018) - Ortega-Palacios, R.; Trujillo-Romero, C. J.; Cepeda Rubio, M. F. J.; Vera, A.; Leija, L.; Reyes, Jose L.; Ramírez-Estudillo, M. C.; Morales-Alvarez, F.; Vega-López, M. A.
Abstract : Microwave ablation (MWA) by using coaxial antennas is a promising alternative for breast cancer treatment. A double short distance slot coaxial antenna as a newly optimized applicator for minimally invasive treatment of breast cancer is proposed. To validate and to analyze the feasibility of using this method in clinical treatment, a computational model, phantom, and breast swine in vivo experimentation were carried out, by using four microwave powers (50 W, 30 W, 20 W, and 10 W). The finite element method (FEM) was used to develop the computational model. Phantom experimentation was carried out in breast phantom. The in vivo experimentation was carried out in a 90 kg swine sow. Tissue damage was estimated by comparing control and treated micrographs of the porcine mammary gland samples. The coaxial slot antenna was inserted in swine breast glands by using image-guided ultrasound. In all cases, modeling, in vivo and phantom experimentation, and ablation temperatures (above 60°C) were reached. The in vivo experiments suggest that this new MWA applicator could be successfully used to eliminate precise and small areas of tissue (around 20–30 mm 2 ). By modulating the power and time applied, it may be possible to increase/decrease the ablation area.